PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV-A SDN MARGOREJO 1/403 SURABAYA MELALUI PERMAINAN JURAGAN KEBUN CERDAS DALAM PEMBELAJARAN BANGUN DATAR - Putri Wihatma Andianti; Rarasaning Satianingsih; Novi Indria Wardani; Okania Sri Purwaningrum; Hanifah Khoirunnisa; Lucky Juniar Rachman; Jauharul Ifadhi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to enhance the critical thinking skills of fourth-grade students at SDN Margorejo 1/403 Surabaya through the implementation of the group educational game "Juragan Kebun Cerdas" in flat geometry lessons. The problem addressed is the students' low ability to apply critical thinking in solving mathematics problems related to the concepts of area and spatial arrangement. This research uses a Classroom Action Research (CAR) approach, conducted in two cycles. The research subjects are fourth-grade students, with data collection techniques including observation, Student Worksheet (LKPD), and individual tests. Interventions are carried out through collaborative game-based learning, followed by individual evaluations to assess the development of students' critical thinking skills. The results show an improvement in critical thinking abilities, as seen in the accuracy of calculations, enhanced analytical skills, and stronger arguments in solving mathematics problems. In conclusion, integrating game-based collaborative learning with structured individual assessments effectively develops students' critical thinking skills in understanding flat geometry.